2-(3-Oxo-3,4-dihydro-2H-1,4-benzothiazin-4-yl)acetohydrazide - Azher Saeed; Zaid Mahmood; Shiyao Yang; Saeed Ahmad; Muhammad Salim (Acta Crystallographica Section E, 2010)
In the title compound, C10H11N3O2S, the thiazine ring exists in a conformation intermediate between twist-boat and half-chair. The dihedral angle between the mean plane of the thiazine ring and the hydrazide group is 89.45 (13)°. In the crystal, N—H...O hydrogen bonds link the molecules into (100) sheets and weak C—H...O interactions further consolidate the packing.